STUDY OF NANOPARTICLES AND ITS IMPACT FOR HUMAN AND ENVIRONMENT (International Journal of Food and Nutritional Sciences, 2022)
It has been observed that Today's society has become completely based on nanomaterials because nanomaterials are proving to be very effective due to their minimum size, therefore they are vital to function and have a strong impact on all areas such as engineering, communication, and medical field, environment, cosmetic and coatings. Although much of nanotechnology is still in the research and development phase, nanomaterials are expected to be used in a wide variety of applications.Currently, nanotechnology revolutionizing both the scientific and industrial communities due to their applications in the fields of medicine, environmental protection, energy, and space exploration. Despite the evident benefits of nanoparticles, there are still open questions about the influence of these nanoparticles on humans and the environment. This is one of the critical issues that must be addressed soon.Nanoparticles are the domain of interdisciplinary and complex, involving the simultaneous use of knowledge in several areas, research in the field of nanomedicine and nanotechnology allows a deeper understanding of human health and the environment. The various forms of nanotechnology have the potential to make a very significant impact on society. New health risks possibly involve quite different mechanisms of interference with the physiology of human and environmental species